Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.eurpsy.2019.04.010
|View full text |Cite
|
Sign up to set email alerts
|

The effects of transcranial direct current stimulation compared to standard bupropion for the treatment of tobacco dependence: A randomized sham-controlled trial

Abstract: Background:Current treatments for smoking cessation are not effective for most smokers. This study aims to examine the effectiveness of transcranial Direct Current Stimulation (tDCS) on smoking cessation.Methods:In this randomized, sham-controlled trial study, tobacco-dependent (by DSM-5) male participants were recruited from the general public invitation. Participants were randomly allocated to 5 groups; (A), treatment with 300mg bupropion for 8 weeks; (B), active tDCS (20 sessions for 4 weeks); (C), sham for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
(61 reference statements)
0
13
1
Order By: Relevance
“…Most importantly, however, no differences were found between the sham and active tDCS group in cigarette consumption and craving. This finding is not in line with a series of previous studies that have demonstrated that tDCS is effective in reducing cigarette smoking [17][18][19][20] and cigarette craving [11,12]. A possible explanation for this unexpected finding is that in the current study craving and cigarette consumption were assessed by means of EMA.…”
Section: Plos Onecontrasting
confidence: 99%
See 4 more Smart Citations
“…Most importantly, however, no differences were found between the sham and active tDCS group in cigarette consumption and craving. This finding is not in line with a series of previous studies that have demonstrated that tDCS is effective in reducing cigarette smoking [17][18][19][20] and cigarette craving [11,12]. A possible explanation for this unexpected finding is that in the current study craving and cigarette consumption were assessed by means of EMA.…”
Section: Plos Onecontrasting
confidence: 99%
“…This effect has been found for a variety of substances, such as tobacco [11,12], marijuana [13], cocaine [14], heroin [15], and alcohol [16]. For tobacco addiction specifically it was found that tDCS could not only reduce craving, but also cigarette consumption [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations